Antiferromagnetic Inverse Spin Hall Effect. Issue 42 (19th September 2022) - Huang, Lin; Zhou, Yongjian; Qiu, Hongsong; Bai, Hua; Chen, Chong; Yu, Weichao; Liao, Liyang; Guo, Tingwen; Pan, Feng; Jin, Biaobing; Song, Cheng
Abstract: The inverse spin Hall effect (ISHE) is one of the accessible and reliable methods to detect spin current. The magnetization‐dependent inverse spin Hall effect has been observed in magnets, expanding the dimension for spin‐to‐charge conversion. However, antiferromagnetic Néel‐vector‐dependent ISHE, which has been long time highly pursued, is still elusive. Here, ISHE in Mn2 Au/[Co/Pd] heterostructures is investigated by terahertz emission and spin Seebeck effect measurements, where [Co/Pd] possesses perpendicular magnetic anisotropy for out‐of‐plane polarized spin current generation and Mn2 Au is a collinear antiferromagnet for the spin‐to‐charge conversion. The out‐of‐plane spin polarization (σ z ) is rotated toward in‐plane by the Néel vectors in Mn2 Au, then the spin current is converted into charge current at two staggered spin sublattices. The ISHE signal is much stronger when the converted charge current is parallel to the Néel vector compared with its orthogonal counterpart. The Néel vector and resultant ISHE signals, which is termed as antiferromagnetic inverse spin Hall effect, can be switched. The finding not only adds a new member to the Hall effect family, but also makes antiferromagnetic spintronics more flexible. Abstract : Inverse spin Hall effect (ISHE) is one of the accessible and reliable methods to detect spin current. ISHE signals dependent on the Néel vector in Mn2 Au/[Co/Pd] are observed, and they are much stronger when the converted charge current is parallel to the Néel vector compared with its orthogonal counterpart. The finding enriches the Hall effect family, and makes antiferromagnetic spintronics more flexible.